A numerical kinematic model of welding process for low carbon steels. (1st July 2017) - Ni, Junyan; Abdel Wahab, Magd
Highlights: Predicting microstructure development of welding low carbon steels. Microstructural model integrated into finite element package ABAQUS. Prediction of volume fractions of each micro-constituents. Proposed model forecasted the transformation products during and after welding. Abstract: A numerical metallurgical integrated model, based on Bhadeshia microstructure model, is developed to predict microstructure development of welding low carbon steels. The new model integrates the thermodynamic kinematics equations and provides the start and finish temperatures during continuous cooling, the transformation kinetics, as well as, the resultant volume fractions of each micro-constituents. Further, it is integrated into finite element (FE) commercial package ABAQUS and the laser welding process of DP600 blanks is numerically simulated. The temperature-dependent thermal properties are adopted to calculate the temperature field and history, which are used as input to describe the kinematics of phase transformation. Knowing the chemical composition in each node, the process of austenization and austenite-to-allotriomorphic ferrite/Widmannstätten ferrite/pealite/bainite/martensite are modelled, respectively. The results obtained using our proposed model are compared with those obtained using Kirkaldy model for S355 steel. Furthermore, the results predicted by both models are compared with experimental data. In addition, the predicted volume fractions are validated using experimental data at selected locations. The proposed thermo-metallurgical model serves as a useful tool to forecast the transformation products during and after welding.